Review : Analisis Kandungan Senyawa Bioaktif Pada Tanaman Tropis Dan Efektivitas Farmakologis - Milla Astari; Nazwa Naila Putri; Syaila Khairunnisa; Latifatus Zahroh; Ardi Mustakim (Journal of Innovative and Creativity, 2026)
Indonesia has a diverse range of tropical plants with potential as sources of bioactive compounds and natural medicines. Tropical plants contain secondary metabolites such as alkaloids, flavonoids, tannins, saponins, phenolics, and terpenoids, which have pharmacological activity. This study aims to examine the bioactive compound content and pharmacological effectiveness of several tropical plants through a literature review. The method used was a non-experimental ethnopharmacological study based on scientific journals. The results showed that most of the plants studied primarily act as antioxidants, as well as other activities such as antimicrobial and anticancer. This indicates that Indonesian tropical plants have great potential to be developed as sources of phytopharmaceutical raw materials